What is the current state of debate around the use of contextualised admissions for undergraduate admissions? A review of the current stakeholder perspective. (2nd January 2021) - Mountford-Zimdars, Anna; Moore, Joanne; Higham, Louise
ABSTRACT: Higher Education Institutions in England are an integral part of the government's social mobility strategy. Contextualisation of undergraduate admissions decisions has emerged as a key tool towards progressing social mobility objectives. The present paper builds on our previous 2013 research by describing findings from 15 qualitative interviews with stakeholders in contextualised admissions. Stakeholders were drawn from government, non-governmental and third sector bodies including those representing the voice of schools and young people. We find that data challenges continue to be a main barrier to the application of contextual admissions. Respondents thought that more consistency and transparency between universities would be helpful to assist applicants and those who support them to better understand contextual data use in undergraduate admissions. Views are divided about whether differential admissions offers represent the most important application of contextual data. Respondents saw potential for using contextual data beyond admissions for supporting students at university and into further study or employment.